diversity intake Knowledge Level, Economic Status and Number of Family Members on Food Diversity Intake at School-Age Children in Banyumas Regency - Katri Andini Surijati; Pramesthi Widya Hapsari; Windri Lesmana Rubai (Insights in Public Health Journal, 2021)
Background Dietary diversity is an indicator of the quality of food intake which is very important to meet the nutritional needs of school-age children to support children's growth and physical development. School-age children (6-12 years) are a very strategic target for health coaching to prepare the next generation who are healthy, independent, productive, qualified, resilient, and able to compete globally. Improving nutrition for primary school children is a strategic step in particular because its impact is directly related to quality human resources (HR) who are ready to compete. Direct factors (diet and infectious diseases) and indirect factors (economic status, maternal knowledge, and several family members) influence the nutritional adequacy of school-age children. Objectives This study aims to look at the relationship between maternal knowledge about nutrition and health, economic status, and the number of family members on food diversity in primary school children in rural and urban areas of Banyumas Regency during the Covid-19 pandemic. Methods This study used a quantitative approach with a cross-sectional design involving 58 elementary school students in Banyumas Regency. Data were collected using an online questionnaire on google form to minimize the transmission of the covid-19 virus outbreak between researchers and students who were respondents of this study. Researchers have provided video tutorials on how to fill out a google form questionnaire to avoid confusion that results in biased data provided. Results The results of this study indicate that most of the mothers' knowledge is still lacking about nutrition and health (63.8%) this can be influenced by the education level of mothers who graduated from high school (43.1%) and most of the mothers are not working or as pure housewives ( 81.1%). knowledge influences the diversity of children's diets (0.44%), economic status (0.009%), and the number of family members (0.26%). Conclusions There is a relationship between the economic status of parents and the diversity of food for school-age children compared to the level of knowledge of the mother and the number of family members Keywords: diversity of food, elementary school children, physical activity